IoT Technologies for HealthCare 9th EAI International Conference, HealthyIoT 2022, Braga, Portugal, November 16-18, 2022, Proceedings - Spinsante, Susanna; Iadarola, Grazia; Paglialonga, Alessia; Tramarin, Federico (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 9th EAI International Conference on IoT Technologies for HealthCare, HealthyIoT 2022, which was held in Braga, Portugal, in November 2022. The 11 full papers and 2 invited papers presented in this volume were carefully reviewed and selected from 37 submissions. The papers are organized in the following topical sections: Analysis of Measurement Data in IoT Technologies for Health; and IoT Applications in Research and Clinical Practice.
Analysis of Measurement Data in IoT Technologies for Health -- Automatic Wardrobe for Blind People -- Heart Rate evaluation by Smartphone: an overview -- A Low-Cost Open-Source Bionic Hand Controller: Preliminary Results and Perspectives -- Preliminary Study on Gender Identification by Electrocardiography Data -- Exploiting Blood Volume Pulse and Skin Conductance for Driver Drowsiness Detection -- Skin Conductance under acoustic stimulation: analysis by a portable device -- IoT Applications in Research and Clinical Practice -- Multivariate Classification of Mild and Moderate Hearing Loss Using a Speech-in-Noise Test for Hearing Screening at a Distance -- A Preliminary Prototype of Smart Healthcare Modular System for Cardiovascular Diseases Remote Monitoring -- Gender classification using nonstandard ECG signals - A conceptual framework of implementation -- Designing a soft-actuated smart garment for postural control and fall prevention in elderly women -- Cultivate Smart and Healthy Ageing -- Application of KNN for Fall Detection on Qualcomm SoCs -- Assessment of human activity classification algorithms for IoT devices.
Keywords: Medical informatics; Artificial intelligence; Application software; Computer systems; Health Informatics; Artificial Intelligence; Computer and Information Systems Applications; Computer System Implementation